2015
DOI: 10.5539/res.v7n4p148
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Demonstrative Behavior Manifestations of Teenagers Brought up in Orphanages

Abstract: Theoretical justification and experimental validation of forms and methods applied for psychologicalpedagogical correction of demonstrative behavior of teenagers brought up in orphanages have become the research objective. 127 pupils of orphanages of the Republic of Tatarstan participated in the experiment To collect the information there were applied two variations of the test for ostentation, methods of mathematical statistics, Student's t-criteria to check hypotheses of mean average precision. The results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A number of studies have identified the connection between family relationships and adolescents suicide tendencies. So, in families where precedence is given to such styles of family education as rejection, authoritarian hypersocialization, infantilization and symbiosis, the risk of adolescent suicide behavior increases significantly (Ribakova & Biktagirova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have identified the connection between family relationships and adolescents suicide tendencies. So, in families where precedence is given to such styles of family education as rejection, authoritarian hypersocialization, infantilization and symbiosis, the risk of adolescent suicide behavior increases significantly (Ribakova & Biktagirova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The issues of risky behavior genesis, the system of factors determining its beginning, and the features of these patterns of personal behavior manifestation have been profoundly studied in the works of such scientists as Breakwell (2007), Fischhoff (1978), Slovic (1978), Lichtenstein (1978), Read (1978), Combs (1978), Trimpop (1994), Bunas (2013), Boldakova (2015), Bocharova (2011), Bykov (2006), Vorobiev (2000), Ilyin (2012), Puzyrevich (2010), Ribakova & Biktagirova (2015), Shumakova et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…In these departments much attention is paid to the psychological rehabilitation of the person. It is recognized that an effective method of social influence to counter delinquent behavior are community service and behavioural therapy in its various forms (Bryanta &;Forsythb, 2012;Cava et al, 2007;Gilinsky, 2004;Kleyberg, 2001Kleyberg, , 2004Linfoot et al, 1999;Mendelevitch, 2004;Mendelevitch & Makaricheva, 2002$;Ribakova .& Biktagirova, 2015).…”
mentioning
confidence: 99%